(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Survey of bone density in patients over 40 years old visiting the Department of Outpatient of VietDuc Hospital. Methods: Cross-sectional descriptive study, examining the bone density of 600 patients over 40 years old by dual-energy X-ray absorptiometry (DEXA) at the lumbar vertebrae, femoral neck. Results: The rate of osteoporosis accounted for 37.33%, pre-osteoporosis 21.33%, of which the average bone density (T-score) was measured at L1, L2, L3, L4, left femoral neck (right) ) are: 0.079 ± 1.22 respectively; -0.23 ± 1.38; 0.01 ± 1.44; -1.13 ± 1.44; 0.22 ± 1.22 (0.35 ± 1.44). The average T-score of men is higher than that of women. The mean T-score of the BMI <18.5 group was lower than that of the BMI ≥ 18.5 group in both men and women. At all measurement sites, there was an inverse relationship between age and bone density, statistical significance. Conclusion: Bone density decreases with age. Women have lower bone density than men. Patients with low BMI had lower bone density than patients with high BMI.